The absence of B lymphocytes reduces the number and function of T-regulatory cells and enhances the anti-tumor response in a murine tumor model - Tadmor, Tamar; Zhang, Yu; Cho, Hyun-Mi; Podack, Eckhard R.; Rosenblatt, Joseph D. (Cancer Immunology, Immunotherapy, 2011)
Increasing evidence suggests that B lymphocytes play a central role in inhibiting the immune response against certain tumors, but the underlying mechanisms by which B cells facilitate tumor growth are still poorly understood. In this study, we investigated how the presence or absence of B cells affects expansion and function of T-regulatory cells (‘T-regs’) in a murine breast tumor model (EMT-6). We compared tumor growth, and the number and function of T-reg cells in wild-type immune-competent mice (ICM) and B-cell-deficient mice (BCDM). Mice were either tumor-naive or implanted with EMT-6 mammary adenocarcinoma cells. Tumor growth was markedly inhibited in BCDM, compared to wild-type mice (ICM). Increased T-reg expansion as defined by CD4+/CD25+/FOXP3+ cells was evident following EMT-6 inoculation in ICM in comparison with non-tumor-bearing mice or compared to BCDM in which tumor had been implanted. The percentage and absolute number of T-regs in the spleen, tumor draining lymph nodes, and tumor bed were significantly reduced in BCDM compared to ICM. T-reg function, measured by suppression and proliferation assays, was also reduced in tumor inoculated BCDM compared to ICM. Our studies indicate that absence of B cells may play a role in augmenting the T-cell anti-tumor response, in part due to effects on T-regulatory cell expansion and function.